Reflection on the revolution of our time - Laski,Harold J. (London, 1952)
THIS book owes an immense debt to my friends, especially to those endless debates at 17 Clarkson Road where my fellow evacuees and he had discussed its problems term after term, since war began, until, with the midnight news, we turned from analysis of principle to speculation upon the event. It owes much, too, to my students who, in the seminars at the London School of Economics and Political Science, have insisted on trying to understand both what they are fighting for and how they can free future generations of students from the curse of war. Much of it has been shaped by the questions and criticisms put to me at Labour Party conferences all over the country, and in those lectures in camp and aerodrome where the determined heckling of soldiers and airmen has taught me how Cromwell's Ironsides became that unbeatable instrument, a thinking army.
Keywords: Democracy